IgG Index Revisited: Diagnostic Utility and Prognostic Value in Multiple Sclerosis - Zheng, Yang; Cai, Meng-Ting; Yang, Fan; Zhou, Ji-Ping; Fang, Wei; Shen, Chun-Hong; Zhang, Yin-Xi; Ding, Mei-Ping (Frontiers in Immunology, 2020)
Objective: Early and accurate diagnosis of multiple sclerosis (MS) remains a clinical challenge. The main objective is to evaluate the diagnostic and prognostic value of the routinely performed immunoglobulin G (IgG) index for MS patients in the Asian population. Methods: A retrospective study was conducted among a cohort of clinically isolated syndrome (CIS) patients in China with known oligoclonal band (OCB) status and IgG index at baseline. We first evaluated the predictive value of IgG index for OCB status. Secondly, the diagnostic utility and prognostic value of IgG index alone were tested. Lastly, we incorporated IgG index into the 2017 McDonald criteria by replacing OCB with either “IgG index or OCB” (modified criteria 1), “IgG index and OCB” (modified criteria 2), or “IgG index” (modified criteria 3). The diagnostic utility of different criteria was calculated and compared. Results: In a CIS cohort in China (n = 105), IgG index > 0.7 forecasted OCB positivity (X2 = 22.90, P < 0.001). An elevated IgG index was highly prognostic of more clinical relapses (1-year adjusted odds ratio [OR] = 1.32, P = 0.015; 2-year adjusted OR = 1.69, P = 0.013) and Expanded Disability Status Scale worsening (1-year adjusted OR = 1.76, P = 0.040; 2-year adjusted OR = 1.85, P = 0.032). Under the 2017 McDonald criteria (Positive Likelihood Ratio = 1.54, Negative Likelihood Ratio = 0.56), an IgG index > 0.7 in CIS patients increased the likelihood of developing MS within 2 years, either when OCB status was unknown (Positive Likelihood Ratio = 2.11) or with OCB positivity (Positive Likelihood Ratio = 2.11) at baseline; An IgG index ≤ 0.7, along with a negative OCB, helped rule out the MS diagnosis (Negative Likelihood Ratio = 0.53). Conclusions: IgG index > 0.7 predicts OCB positivity at the initial attack of MS and is prognostic of early disease activity. IgG index serves as an easily-obtainable and accurate OCB surrogate for MS diagnosis in the Asian population.